Analysis of Hydroponic System Crop Yield Prediction and Crop IoT-based monitoring system for precision agriculture - M, Sathanapriya; Devi, R. Prameela; Sandhya, C.; Pokuru, Anil; HabeeburRahman, T.; Jose, Bibin K; Gadde, Samata (2022 International Conference on Edge Computing and Applications (ICECAA), 2022)
IoT is the necessary revolution in every industry. Any task is made simple when it can be observed and managed remotely. Every technical advancement should be undertaken in agriculture because it is such an important subject. The demand for agriculture has dramatically expanded due to the expansion in global population, but sadly, farmers are unable to meet the unending demand. IoT will be a better option than expanding the scale of agriculture.By cutting down on waste, precision agriculture can increase the output of any crop. The proposed work accomplishes this by keeping an eye on environmental factors that influence crop growth, such as temperature, humidity, soil moisture, etc. It also assists farmers in selecting an idle crop that will work best for them based on the information gathered and the environmental circumstances. The danger of crop failure, low yield, excessive water consumption, excessive fertiliser and pesticide use, etc. can be greatly decreased with this model, making it more effective than previous methods.The information gathered by the network nodes placed across the field is transmitted to the cloud, where it is evaluated and displayed for farmers' use. Farmers may make accurate and effective decisions that will affect their crops with the use of displayed data.